Segmentasi Konsumen pada Pasar Online di Indonesia - Lailatul Hijrah (FORUM EKONOMI, 2017)
This research aims to analyze market analysis Online based online consumer segmentation, profile and their characteristics. In the first stage of this study conducted a survey related to the Online consumer behavior literature, then perform cluster analysis and segmentation Online consumer spending behavior. A sampel of 328 respondents collected by mail survey. In order to perform segmentation according to usage patterns internet can use descriptive method non-overlapping post-hoc, this method is used to identify segments in accordance with the pattern of internet usage. Results showed that the consumer market Online consists of three segments that are generally commonly used are: segmentation pattern Basic Communication, in this segment of consumers who use the Internet primarily to communicate via e-mail, then the segment of Commerce or shopping in this segment of consumers who using the internet to surf and look around online stores and third segments of social relationships and pleasure, in this segment of consumers who exploit the internet using interactive features to interact and entertainment by way of chatting, blogging, video streaming, gaming, stalking and downloading. Limitations include data collected through a survey whose information comes from the Internet, so it takes the views of other parties who are not users but observers Online businesses that have other opinions on this segmentation. Later on this segmentation actually still can be broken down into several sub-segments, as continued research efforts.Keyword: Internet use pattern, segment, online sonsumer